Biostatistical Design and Analysis Using R. - Logan, Murray (John Wiley & Sons, 2010)
R - the statistical and graphical environment is rapidly emerging as an important set of teaching and research tools for biologists. This book draws upon the popularity and free availability of R to couple the theory and practice of biostatistics into a single treatment so as to provide a textbook for biologists learning statistics, R, or both. An abridged description of biostatistical principles and analysis sequence keys are combined together with worked examples of the practical use of R into a. complete practical guide to designing and analyzing real biological research. Topics covered inc.